A symbol approach for classification of molecule-based magnetic materials exemplified by coordination polymers of metal carboxylates - Zheng, Yan-Zhen; Zheng, Zhiping; Chen, Xiao-Ming (Coordination chemistry reviews, 2014)
•We proposed a novel symbol approach for classification of molecular magnets.•This approach provides a concise feature for labelling molecular magnets.•The symbols can simplify the searching for certain molecular magnetism.•We reviewed recent examples of magnetic metal-carboxylate coordination polymers.•The construction of low-dimensional magnets has been focused. The ever-growing family of molecule-based magnetic materials calls for a systematic classification of these structurally sophisticated and magnetically diverse compounds. Using magnetically active coordination polymers of metal carboxylates as representatives, we propose and illustrate in this review a symbol approach for their organization and categorization. By adopting this approach, the seemingly complex magneto-structural correlations in a wide variety of molecular magnetic materials, including single-molecule magnets, single-chain magnets, geometrically frustrated magnets, and high Curie-temperature magnets, can be readily discerned.